Study on the effects of land use changes to the urban Hydrology of Tarlac City, Tarlac - Mercado, Jose Victor M. (Animo Repository, 2014)
Tarlac City has a great potential to be the center of commerce and trade for the whole Tarlac Province. For this reason, the city government implemented its Comprehensive Land Use Plan which states a drastic change in land use percentages between the current and proposed plans. The study aims to evaluate the influence of the land use changes in the City by hydrologic and hydraulic analysis. The group developed current and proposed land use maps using Q-GIS and performed simulations in HEC-HMS and SWMM models. The output of the study is from the analysis of the watershed response of the study area and the drainage adequacy of the drainage system. The group found that the hydrographs generated from the study area had an insignificant change in almost the entire watershed. Also, the group was able to determine the inadequate canal segments in the drainage network in the Central Business District. Lastly, the group would like to recommend solutions to the study such as increasing the amount of previous areas in the watershed and also recommend conducting further studies to produce more accurate and refined results.